CARDIOVASCULAR RISK IN RHEUMATOID ARTHRITIS- A COMPREHENSIVE REVIEW OF MECHANISMS, ASSESSMENT, AND MANAGEMENT - Magdalena Morytko; Szymon Rudawski; Magdalena Zięba; Maja Elertowicz; Mikołaj Moskwa; Patrycja Herod; Aleksandra Wójciak; Kateryna Shtohryn (International Journal of Innovative Technologies in Social Science, 2025)
Rheumatoid arthritis (RA) is a systemic inflammatory condition associated with a markedly increased risk of cardiovascular (CV) morbidity and mortality, approximately 1.5-2- fold higher than in the general population. Chronic systemic inflammation, immune dysregulation, and increased oxidative stress in RA contribute to accelerated atherosclerosis, endothelial dysfunction, and cardiac remodeling. Conventional CV risk factors- such as dyslipidemia, hypertension, diabetes, and smoking- are also more prevalent in RA, further amplifying vascular injury. Despite advances in understanding these mechanisms, CV disease remains the leading cause of death among patients with RA. Traditional risk assessment tools are often insufficient in RA, highlighting the need for improved risk stratification and preventive strategies. Current management focuses on early and aggressive control of inflammation using disease-modifying antirheumatic drugs (DMARDs) to achieve remission or low disease activity. According to recent European League Against Rheumatism (EULAR) recommendations, coordinated multidisciplinary care involving both rheumatology and cardiology is essential for early detection and prevention of CV complications. Patient education, lifestyle modification, and stringent management of modifiable risk factors are key strategies that can significantly reduce CV events and improve long-term outcomes in RA.Materials and methods: This narrative review aims to address current knowledge on cardiovascular risk in rheumatoid arthritis, including underlying mechanisms, assessment methods, and management strategies. A nonsystematic literature search of PubMed, Embase, and Directory of Open Access Journals (DOAJ) was conducted in August 2025 using keywords such as “rheumatoid arthritis”, “cardiovascular disease”, “cardiovascular risk”, “atherosclerosis”, “disease-modifying antirheumatic drugs”. Studies published between 2000 and 2025 were considered. Peer-reviewed original research articles and systematic or narrative reviews written in English were included based on their relevance to the topic.